Structural Analysis of PfSec62-Autophagy Interacting Motifs (AIM) and PfAtg8 Interactions for Its Implications in RecovER-phagy in Plasmodium falciparum - Mamidi, Ashalatha Sreshty; Ray, Ananya; Surolia, Namita (Frontiers in Bioengineering and Biotechnology, 2019)
Autophagy is a degradative pathway associated with many pathological and physiological processes crucial for cell survival. During ER stress, while selective autophagy occurs via ER-phagy, the re-establishment of physiologic ER homeostasis upon resolution of a transient ER stress is mediated by recovER-phagy. Recent studies demonstrated that recovER-phagy is governed via association of Sec62 as an ER-resident autophagy receptor through its autophagy interacting motifs (AIM)/LC3-interacting region (LIR) toAtg8/LC3. Atg8 is an autophagy protein, which is central to autophagosome formation and maturation. Plasmodium falciparum Atg8 (PfAtg8) has both autophagic and non-autophagic functions critical for parasite survival. Since Plasmodium also has Sec62 in the ER membrane and is prone to ER stress due to drastic transformation during their complex intraerythrocytic cycle; hence, we initiated the studies to check whether recovER-phagy occurs in the parasite. To achieve this, a comprehensive study based on the computational approaches was carried out. This study embarks upon identification of AIM sequences in PfSec62 by carrying out peptide-protein docking simulations and comparing the interactions of these AIMs with PfAtg8, based on the molecular dynamic simulations. Detailed analysis is based on electrostatic surface complementarity, peptide-protein interaction strength, mapping of non-covalent bond interactions and rupture force calculated from steered MD simulations. Potential mean forces and unbinding free energies (ΔGdissociation) using Jarzynski’s equality were also computed for the AIM/LIR motif complexes with PfAtg8/HsLC3 autophagy proteins to understand their dissociation free energy profiles and thereby their binding affinities and stability of the peptide-protein complexes. Through this study, we predict Sec62 mediated recovER-phagy in Plasmodium falciparum, which might open new avenues to explore novel drug targets for antimalarial drug discovery.